A velocidade de ajuste das necessidades de capital de giro: um estudo sobre amostra de empresas listadas na BM&FBovespa - Salerno, André (2014)
The main objective of this study is to evaluate some determinants of working capital needs commonly studied in literature and to analyze how companies are moving toward a goal (target) of NTC. Such study is unprecedented in Brazil, as far as we know. In fact, there is a lack of substantial theories on working capital in the finance area and very few studies can be found. Those who choose to study this subject may see that due to its current stage, it has been researched with the support of more consolidated theoretical bases, such as capital structure. These studies have widely used the concept of goal/target to determine the optimal capital structure and the speed this structure adjusts itself to in order to optimize its resources. The fact that such definitions and/or more established theories on the topic do not exist yet set this study in motion. It uses speed adjustment towards a working capital goal as well as the Partial Adjustment Model (PAM) and the Generalized Method of Moments (GMM) as techniques to support this goal. With this unprecedented combination in the Brazilian market when it comes to working capital, we hope to bring new contributions to the academic and business communities. In order to get the data for this quantitative study, we used existing information from Economatica® and BCB - Central Bank of Brazil. These databases use the quarterly financial statements between the periods of December 21st 2007 to June 30th 2014 (adjusted by inflation - IPCA) of companies listed on the BM&FBovespa which have at least 15 consecutive periods (quarters) of data. A total of 2,000 observations and 105 companies were studied. As for the method, the Dynamic Data Panel (unbalanced) was used as well as the following techniques in order to reach the main goal of the study ('What is the speed of adjustment in Working Capital Requirement?'): the Partial Adjustment Model technique for the analysis of determinants of working capital needs and movement towards a goal and the Generalized Method of Moments (GMM) technique to control possible effects of endogeneity (BLUNDELL and BOND, 1998) and to solve problems with residual autocorrelation (PIRES, ZANI e NAKAMURA, 2013, p. 19)